STUDENTS AND READINESS TO FACE THE WORLD OF WORK - Hidayah, Dita Nisaul (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
This article examines students' readiness to face the world of work. As stated by the Indonesian Minister of Education and Culture, Nadiem Anwar Makarim, B.A., M.B.A., that 80% of Indonesian students do not work according to their major. This statement suggests that the diploma obtained is not in accordance with the demands of the world of work. So the problem is how the government will try to resolve the gap between graduates and employment opportunities. And how prepared students are to face the world of work after graduating.  The article is based on the results of random online open interviews with students at several universities in Surabaya. The results of the interviews show that students generally want to be able to work according to the disciplines they obtained at college or the diploma they obtained. And students hope that there will be efforts from the government to create jobs that suit their majors or changes to the curriculum that lead to a connection between education and work life.